Economic development opportunities in well-functioning settlements - Tóth , Tamás (Studia Mundi – Economica, 2018)
I have chosen this topic to highlight the decisive role of local governments, and in particular the settlement leaders, in forming regional policies. The settlement leadership’s way of thinking and their ideas are very important driving forces behind the development of the settlement. Nowadays Settlement Development and Regional Economic Development raise some crucial questions, like: “What is a good local government and a good settlement? How could that be described?” This study explores a best practice for a local economic development research and for successful community leadership, while discussing the importance of local actors.